Bringing back psychological empowerment in empowerment-oriented leadership: the development of the Psychological Empowerment Leadership Scale (PELS) - Schermuly, Carsten C.; Algner, Mona; Lorenz, Timo (Frontiers in Psychology, 2025)
Empowering leadership has garnered significant attention over the past two decades, driven by the evolving dynamics of organizations. However, current measures of empowering leadership often fail to align with the psychological empowerment construct (Spreitzer, 1995) – the very construct these leadership practices claim to impact – and exhibit some psychometric flaws. To address these issues, we introduce the Psychological Empowerment Leadership Scale (PELS), designed to assess leader behaviors fostering psychological empowerment across six dimensions. We used automated item selection algorithms to ensure high psychometric quality and tested the instrument’s validity and measurement invariance in German and US samples. A second study with two measurement points, assessed the criterion-oriented validity of the PELS. Confirmatory factor analyses support its factorial validity and indicate metric measurement invariance across both countries. The PELS shows strong correlations with psychological empowerment, job satisfaction, and emotional exhaustion, often exceeding previous meta-analyses, thus demonstrating criterion validity. However, its association with innovative behaviors was lower than expected, warranting further research. With only 24 items, the PELS, offers high reliability and stability over time, providing a more efficient tool for assessing empowering leadership and aligning better with contemporary theoretical perspectives. This research refines the conceptualization and assessment of empowering leadership in contemporary organizational contexts.